[RETRACTED] Conservation status of sharks and rays caught in Indonesian Fisheries Management Area 712 - TRI DJOKO LELONO; GATUT BINTORO; ARIEF SETYANTO; DADUK SETYAHADI; DARMAWAN OKTO SUTJIPTO; WIRASTIKA ADHIHAPSARI; DIAN ALIVIYANTI; ANDIK ISDIANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Lelono TD, Bintoro G, Setyanto A, Setyahadi D, Sutjipto DO, Adhihapsari W, Aliviyanti D, Isdianto A. 2024. Conservation status of sharks and rays caught in Indonesian Fisheries Management Area 712. Biodiversitas 25: 2603-2614. Elasmobranchs, including sharks and rays, are some of the most vulnerable marine fish and are particularly at risk from fishing pressure. Sharks and rays landing data that listed in the Convention on International Trade in Endangered Species (CITES) appendices and/or assessed as in The International Union for Conservation of Nature (IUCN) Red List threatened categories were collected from July to October 2023 at two sites in Indonesian Fisheries Management Area (FMA) 712, East Java, Indonesia, namely Pelabuhan Perikanan Nusantara (PPN) Brondong at Lamongan District and Pelabuhan Perikanan Pantai (PPP) Muncar at Banyuwangi. Stingray species designated as Critically Endangered (CR), Endangered (EN), or Vulnerable (VU) were recorded at both landing sites. More IUCN Red List threatened ray species were recorded at Brondong than at Muncar. Based on Brondong's international trade status, ray species landed at Brondong are at higher risk of extinction than those landed at PPP Muncar. Six shark species are currently listed in CITES Appendix II: A pelagicus, A. superciliosus, S. lewini, S. zygaena, C. falciformis, and I. oxyrinchus. At PPP Muncar, two of these species were traded. Sharks landing at Muncar included species in IUCN Red List categories, while those landing at Brondong were in four categories. Two CITES categories regulate the capture of sharks landed at PPP Muncar and PPN Brondong. At both sites, numerous species with conservation statuses of CR, EN, VU, and NT are still caught. In conclusion, exploitation and insufficient control threaten the shark and ray populations in PPP Muncar and PPN Brondong. To save these species, conservation efforts should prioritize trade monitoring, habitat protection, and stricter laws.